Physicochemical Properties of Four Tomato Cultivars Grown in Nigeria - Adedeji, Olubukola; Taiwo, Kehinde A.; Akanbi, Charles T.; Ajani, Ruth (Blackwell, 2014)
The physicochemical characteristics of tomato fruits from three commercial cultivars available in the local market were compared with a wild cultivar. The results showed that the Ibadan-Local and Wild cultivars had a higher fruit yield than Ife-1 and Roma-VF cultivars. The wild cultivar has a high skin and seed content. The shape of the fruits varied from spherical to pear-like. Physicochemical properties such as specific gravity, pH, titratable acidity, ash and refractive index did not vary significantly while total solids, longitudinal (stem  blossom end) and cross-sectional diameters (transverse diameter), vitamin C and reducing sugars were significantly different (P > 0.05) among the cultivars investigated. The results showed that the wild cultivar has attributes (i.e. physicochemical characteristics) comparable to commercial cultivars to recommend it to breeders for cultivation.